Identification of a 17000 Molecular Weight Antigenic Polypeptide in Transmissible Gastroenteritis Virus-infected Cells - Wesley, R. D.; Woods, R. D. (Journal of General Virology, 1986)
Summary Pulse labelling of cells with [35S]methionine at different times after infection followed by SDS-PAGE was used to resolve and to identify polypeptides designated as specific to transmissible gastroenteritis virus (TGEV)-infected swine testicular (ST) cell cultures. The major TGEV structural proteins, with apparent molecular weights of 200000 (200K), 47K and 30K were detected in radiolabelled cell extracts by 6 h post-infection. Additionally, a 17K major polypeptide was present in infected cells but not in mock-infected control cultures. Labelling with [3H]glucosamine revealed only the 200K and 30K proteins to be glycosylated. TGEV-primed porcine lymphocytes, secondarily stimulated in vitro with sucrose gradient-purified virus, produced antibody only to the two glycoproteins (gp) indicating that the 17K polypeptide is not a surface feature of the virion. Two pigs were infected oronasally with the virulent Miller strain of TGEV and their sera were analysed by immunoprecipitation. At 25 days post-infection convalescent sera responded strongly to gp30 and gp200 and there was a weak initial response to the 17K polypeptide. Serum immunoglobulins at 60 days post-infection reacted strongly to the 17K protein while the antibody response to gp30 was significantly reduced and that to gp200 was slightly reduced.
Keywords: TGEV